De sol, d’air, d’eau sous photons - Catherine Mosbach; Agnès Daval (Projets de Paysage)
This article is a dialogue initiated by Agnès Duval on what Catherine Mosbach considers to be the fundamentals of the landscape. The realisation of landscape projects calls on science and the imagination through experimentation in the field based on an exploratory design. These fundamental notions are illustrated here through the examples of major projects such as the archaeological park of Solutré, the botanical gardens of Bordeaux, the museum of Louvre-Lens and the Phase Shifts Park of Taichung in Taiwan currently being built. Challenged by the singularity of each programme, each site, and each context in which she practises her profession as a landscape architect, Catherine Mosbach cultivates an appetite for much vaster metamorphoses than those which may be approached through the first stone in the landscape edifice, the drawing. Lines, volumes, mock-ups, and field experiments are rooted in a sensory and imaginary experience. The metamorphosis of an embodied design results from casting off envelopes, and reformulating codes of representation as well as leisure uses. A vision of the world and of the landscape project is revealed which is transverse and full of different potentialities. It is deployed with the view of capturing these phenomena and of registering them without any conventional limitations in order to allow impromptu developments.